Powder X-ray diffraction and X-ray photoelectron spectroscopy of cutin from a 300 Ma tree fern (Alethopteris pseudograndinioides, Canada) - Stoyko, Stanislav S. (2013)
Experimental results of X-ray diffraction and X-ray photoelectron spectroscopy of fossil cutin from the compressed foliage of the Carboniferous tree fern Alethopteris pseudograndinioides, Cantabrian age, Sydney Coalfield, Canada, are presented in this paper. The light-colored cutin was obtained by oxidizing the compression in Schulze's solution in two stages for a total of 19 days. The broad peak in the powder diffractogram at 20° is characteristic of an average separation of ~4.4 Å between the methylenic hydrocarbon chains (CH2)n, whereas the sharper peaks at 26°–28° suggest that within a small fraction of the sample, the chains are more regularly separated. Most of the chains are likely randomly aligned to form a nematic structure. Elemental composition by mass amounts to 58.3% C, 1.1% N, 19.4% O, 19.7% Cl, and 1.5% Si, and the local chemical environment of C 1s, O 1s, and Cl 2p is probed. Cl content is a surprising result, and further research is needed for identifying chlorine-containing species.